2005
DOI: 10.1016/j.ejvs.2004.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Abdominal Aortic Aneurysms

Abstract: Aneurysm development is multifactorial with important genetic and environmental factors. The literature supports the theory that IAAA arise from the same antigenic stimulus that is responsible for the non-IAAA, representing one extreme of an inflammatory spectrum. The results after open repair have improved and there is now little difference in the mortality between non-IAAA and IAAA repair. However, there is likely to be a role for endovascular stenting in IAAA management and this requires further study. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
135
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(142 citation statements)
references
References 55 publications
2
135
0
5
Order By: Relevance
“…A recent review reported an increased prevalence of Chlamydia, Herpesvirus and Cytomegalovirus in IAAA [14]. Along similar lines, an experimental study demonstrated significant macrophage infiltration in aortic aneurysms following exposure of rabbits to Chlamydia antigens, a finding that was prevented by Azithromycin [15].…”
Section: Discussionmentioning
confidence: 57%
“…A recent review reported an increased prevalence of Chlamydia, Herpesvirus and Cytomegalovirus in IAAA [14]. Along similar lines, an experimental study demonstrated significant macrophage infiltration in aortic aneurysms following exposure of rabbits to Chlamydia antigens, a finding that was prevented by Azithromycin [15].…”
Section: Discussionmentioning
confidence: 57%
“…16 Computed tomography does have one major disadvantage: it exposes the patient to radiation. 16,38 Magnetic resonance angiography yields similar results to those of computed tomography without exposure to ionizing radiation, but high cost and limited availability have prevented widespread adoption of this modality. 16,38 CONCLUSION A lthough the majority of individuals with AAA are asymptomatic at the time of diagnosis, some patients do present with a history and clinical presentation suggestive of AAA.…”
Section: Discussionmentioning
confidence: 64%
“…6,22,28 If the presence of an AAA is confirmed with ultrasound imaging, a computed tomography scan is the preferred imaging progression. 16,38 While the sensitivity and specificity of computed tomography imaging of the abdomen are lower than that of ultrasound imaging (sensitivity, 0.79-0.90; specificity, 0.77-0.91), 36 it can detect additional aneurysms, evaluate the surrounding organs, and provide details on arterialwall characteristics (dissection, rupture, or thickening). 16 Computed tomography does have one major disadvantage: it exposes the patient to radiation.…”
Section: Discussionmentioning
confidence: 99%
“…73) On the other hand, Tang, et al had a different opinion, suggesting that the thickened inflammatory aneurysmal wall protects itself from rupture risk and corticosteroid therapy may increase rupture risk by weakening the aneurysmal wall. 82) Periaortitis/Periarteritis: Periaortitis and periarteritis are generally classified as inflammatory or infectious conditions. Inflammatory periaortitis and periarteritis include giant cell arteritis, Takayasu arteritis, rheumatoid arthritis, systemic lupus erythematosus (SLE), HLA-B27 associated spondyloarthropathies, ANCA associated vasculitides, Behcet disease, Cogan syndrome, relapsing polychondritis, sarcoidosis, and isolated aortitis such as IgG4-related aortitis or arteritis.…”
Section: Igg4-related Cardiovascular Diseasementioning
confidence: 99%
“…25,82,106) The therapeutic corticosteroid doses for IgG4-related disease are still unclear. Generally, high-dose corticosteroid therapy is started, tapered over a few months, and then a maintenance dose is administered for several years.…”
mentioning
confidence: 99%